Study on Surface Improvement of the Fixed Mold for Wear Resistance by Salt Bath Nitrocarburizing Hardening Process - Trakunsaranakom, Chanyut (Princess of Naradhiwas University Journal, 2019)
This research aims to study on surface improvement of the fixed mold for wear resistance by salt bath nitrocarburizing hardening process. It’s to improve the properties of the mold surface to become more stiffness to be suitable for pelletizing of organic fertilizer. This research was conducted using 12 pieces of mold and divided into 3 groups as follows: 1. The mold has not been hardened amount 4 pieces. 2. The mold was hardened by salt bath nitrocarburizing hardening process with temperature 580 degree Celsius, 4 pieces of hardening time 180 minutes and 4 pieces of 300 minutes. The hardness depth measurement of specimen by using vickers hardness tester which the hardness depth measurement for every 0.01 millimeters, amount 12 points. The specimen has highest surface hardness at distances 0.01 millimeters. It takes time for hardening 180 minutes and 300 minutes which it has hardness 580 HV and 590 HV respectively. Each mold must to pass the pelletizing of organic fertilizer about 5 tons for test wear of mold. The results showed that the mold has not been hardened, there is abrasion wear caused by the metal surface friction. Mold that has not been hardened with a wear rate of 0.68 millimeters and the mold that has been hardened by salt bath nitrocarburizing hardening process that takes time to harden 180 and 300 minutes with a wear rate of 0.28 mm. and 0.23 mm. respectively.